BLOOD TRANSFUSION AS A BASIS FOR THE TREATMENT OF POSTPARTUM HEMORRHAGE - Pakhomova, J.E.; Abdullaeva, M.J. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. Postpartum hemorrhage (PPH) remains one of the leading causes of maternal mortality worldwide. According to the World Health Organization, thousands of women die each year from complications associated with PPH, especially in countries with limited access to health care. Early diagnosis, timely intervention and knowledge of risk factors are critical to saving the life of the woman in labor. From the materials studied, postpartum hemorrhage in the United States is as high as 3.9% for natural childbirth and 6.4% for cesarean section, according to the American College of Obstetricians and Gynecologists. Studies on genetic factors associated with postpartum hemorrhage (PPH) have shown new opportunities for predicting and managing this serious complication. Purpose of the study. To evaluate approaches to blood loss estimation and validity of blood transfusion and blood products in a retrospective analysis comparing 3 years of age, as well as to determine the efficacy of applied methods of treatment of PPK cases in an obstetric hospital. Materials and Methods of Study. A retrospective study of medical records of 70 women diagnosed with postpartum atonic hemorrhage of varying degrees of severity between January 2022 and December 2024, based on the obstetric department of 2 maternity complex was conducted. 2022 (30 histories), 2023 (12 histories) and 2024 (28 histories) All women were diagnosed with postpartum atonic hemorrhage of varying severity. Detailed information on gynecologic and obstetric anamnesis, data on the present pregnancy, concomitant somatic pathology, results of additional investigations, and information on the course of labor were studied. All patients were divided into groups depending on the cause of bleeding: uterine atony, hemostasis disorder. Results: Women diagnosed with postpartum hemorrhage after delivery were included in the study. We studied detailed information of gynecologic and obstetric history, data on the present pregnancy, results of additional investigations, information on the course of labor, amount of blood loss. We identified the leading risk factors that would reduce the incidence of PC. The most important risk factors were: women’s age, multiple pregnancies, large fetus, polyuria, uterine hypotonia in the history, low level of preparation of women for labor in rural areas, repeatedly pregnant women with uterine scars, etc., as well as the following. We also proposed preventive and diagnostic measures that will reduce the frequency of this pathology.